Comparative Indo-European linguistics : an introduction - Beekes, R. S. P. (Robert Stephen Paul) (John Benjamins Pub. Co., 2011)
This book gives a comprehensive introduction to Comparative Indo-European Linguistics. It starts with a presentation of the languages of the family (from English and the other Germanic languages, the Celtic and Slavic languages, Latin, Greek and Sanskrit through Armenian and Albanian) and a discussion of the culture and origin of the Indo-Europeans, the speakers of the Indo-European proto-language. The reader is introduced into the nature of language change and the methods of reconstruction of older language stages, with many examples (from the Indo-European languages). A full description is gi.